MEDIEVAL JEWELERY TOOLS FROM NORTHEASTERN BULGARIA: MEDIEVAL JEWELERY TOOLS FROM NORTHEASTERN BULGARIA - Doncheva, Stella; Tihov, Tihomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
In 2009, the museum in Shumen received a collection of medieval metalworking tools. Most of them are related to jewelry practice and the production of metal products from precious metals and copper alloys. The collection includes tools of various shapes and practical purposes, including jewelry hammers, pliers, cutters, flutes, drills, punches, etc. The presentation of this rich and diverse collection of iron tools is made with a view to jewelry technology, which requires a strictly defined and specific set of tools to be applied in practice. Some of the tools turn out to be very stable forms, having preserved their character and purpose over time until the late Middle Ages and the modern era. The discovery of many examples from the late periods and modern practice significantly assist in the functional determination of most of the tools found in the production centers in the vicinity of Preslav. The traditions established over time show the conservative spirit in the development and changes of most of the foundry and metalworking practices, perfectly mastered and applied by Bulgarian craftsmen. The fact that even today, modern jewelers observe and follow the basic principles of this craft is indicative. The purpose of some of the tools found during the studies is determined precisely by their long-term use, which dates back to ancient times. If there are any changes, they are insignificant and are mainly expressed in the use of some modern tools and materials in order to facilitate and accelerate the work process, rather than to change it in its essence.